IMPLEMENTASI PROBLEM BASE LEARNING BERBANTU MICROSITE S.ID PADA PEMBELAJARAN IPS UNTUK MENINGKATKAN LITERASI DIGITAL DAN LITERASI BUDAYA KEWARGANEGARAAN - Zahroq, Erma Laelatul; Suciptaningsih, Oktaviani Adhi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The development of science and technology in the 21st century makes it easier for students to obtain and access various information, but it has negative impacts such as hoax news, cyberbullying, violent content and disinformation. Literacy is important in the era of technological progress. Good literacy will increase students' understanding in receiving accurate information. It is necessary to increase literacy through the use of models and media in the learning process. This research aims to analyze the implementation of the Problem Based Learning learning model assisted by Microsite s.id in social studies learning to increase Digital Literacy and Cultural Citizenship Literacy. This research uses a Classroom Action Research (PTK) design with a quantitative approach. This research consists of two cycles, consisting of planning, action, observation and reflection. The research subjects were 31 students in class VII-B of SMP Negeri 1 Malang. Based on the data, it is known that learning completion has increased from pre-cycle as many as 14 students with a percentage of 45%, increased in cycle I to 19 students with a percentage of 61%, and in cycle II there was an increase to 31 students who completed their studies with a percentage of 100%. It can be concluded that the implementation of the problem based learning model assisted by the S.ID Microsite can increase Digital Literacy and Cultural Citizenship Literacy, seen from skills in using technology as well as the ability to understand, respect and appreciate the social environment as part of a culture and nation.